Algorithm Game Theory and Mechanism Design - Ranjan Das, Satya; Sahu, Srikant (International Journal of Psychosocial Rehabilitation, 2025)
Algorithm game and mechanism design is a fields of game theory that aim to develop games. Online mechanism extend the methods of mechanism design to dynamic environment with multiple agents. Decisions must be made as information about types is revealed online and without knowledge of the future in the sense of online algorithms. This paper consider algorithm design, enhancement, and improvement of evolutionary computation as a mechanism design problem. This primary principle can be implemented in any evolutionary computation algorithm that need to consider strategy selection issues in its optimization process. The final objective of our work is to solve evolutionary computation design as an algorithmic mechanism design problem and establish its fundamental aspect by taking this perspective. This paper apply the standard tools of mechanism design to algorithm problems and in particular to the shortest path problem